Factors that contribuite to greater church performance for the seventh-day adventist church in the southeastern coference - Gutiérrez, Karla Saraí; Paul, Donald (Anuario de Investigación UM, 2020)
The empirical model in which authentical leadership, church spirituality, church culture and financial performance are predictors of church performance within the Southeastern Conference of Seventh-day Adventist Church in Florida, USA?